"Instrukcja Episkopatu Polski w sprawie udzielania posługi lektora i akolity świeckim mężczyznom z 2007 r." jako forma realizacji postanowień Kodeksu prawa kanonicznego z 1983 r. - Janczewski, Zbigniew (Prawo Kanoniczne, 2009)
Before 25 years pope John Paul II was promulgating the new Code of Canon Low. The Code gives many prerogatives to Episcopal Conferences. One of prerogative is in canon 230 paragraph 1: “lay men whose age and talents meet the requirements prescribed by decree of the Episcopal Conference, can be given the stable ministry of lector and of acolyte, through the prescribed liturgical rite”. “Episcopate of Poland Instruction about to give a lay man the ministry of lector and acolyte”, passed 2 of September 2007. This Instruction introduced in Poland stable ministry of lector and acolyte. This document defines accurately qualities of candidates to ministry. Instruction decides that they must to receive formation and enumerates tasks of lectors and acolytes during celebration of the Holy Mass and another sacraments. Diocesan bishop can forbid lector and acolyte to perform his ministry. Instruction Episcopate of Poland gives information about such examples.